Feeding ecology of the endangered Asiatic wild dogs (Cuon alpinus) across tropical forests of the Central Indian Landscape - Pallavi Ghaskadbi; Neetu Bathla; Aishwarya Bhandari; Shrushti Modi; Parag Nigam; Bilal Habib (Scientific Reports, 2022)
Abstract Studies on resource utilisation by carnivores are essential as they aid in assessing their role in a community, by unravelling predator–prey relationships. Globally, prey depletion is one of the primary causes of declining Asiatic wild dog (dhole) populations. Therefore, it is essential to examine their diet across their range. Our study presents insights into dhole feeding ecology across multiple sites from the central Indian landscape of Maharashtra, India, for the first time. We conducted scat analysis using a subset of genetically identified scats and collected additional data from kills observed while tracking radio-collared dholes and other known packs from 2 study sites. We analysed 861 scats, and 191 dhole kills to identify species and age class of prey. We estimated the relative contribution of various prey, utilising non-linear biomass models of prey consumption. Overall, wild ungulates like sambar and chital were the principal prey in terms of biomass (sambar 61.08%; chital 19.08%) and number of prey consumed (sambar 39.28%; chital 13.83%). An analysis of kill data also suggested that dholes strongly preferred the two deer species; and differential selection of age classes was observed at the 2 study sites. Our study can potentially help manage and conserve this important population of an endangered carnivore.